Moral trauma, moral distress, moral injury, and moral injury disorder: definitions and assessments - Tyler J. VanderWeele; Tyler J. VanderWeele; Jennifer S. Wortham; Lindsay B. Carey; Brendan W. Case; Richard G. Cowden; Richard G. Cowden; Charlotte Duffee; Kate Jackson-Meyer; Francis Lu; Seth A. Mattson; Robert Noah Padgett; et al. (Frontiers in Psychology)
We propose new definitions for moral injury and moral distress, encompassing many prior definitions, but broadening moral injury to more general classes of victims, in addition to perpetrators and witnesses, and broadening moral distress to include settings not involving institutional constraints. We relate these notions of moral distress and moral injury to each other, and locate them on a “moral trauma spectrum” that includes considerations of both persistence and severity. Instances in which moral distress is particularly severe and persistent, and extends beyond cultural and religious norms, might be considered to constitute “moral injury disorder.” We propose a general assessment to evaluate various aspects of this proposed moral trauma spectrum, and one that can be used both within and outside of military contexts, and for perpetrators, witnesses, victims, or more generally.